TEXTILE INDUSTRY WASTEWATER TREATMENT WITH A COMBINATION OF ANAEROBIC MEMBRANE BIOREACTOR AND AEROBIC PROCESS - Kevin Daniel, Jonatan
Textile wastewater is one of the most poluted wastewater. It contains high BOD and COD, strong organic colorant, and low biodegradability level. Color is very easy to degrade biologically by anaerobic treatment. However, aerobic treatment is still needed to mineralize aromatic amines produced from anaerobic treatment. Technologies of anaerobic processes in textile wastewater treatment generally have mayor drawback in washout. This drawback an be overcome by the use of anaerobic membrane bioreactors (AnMBR). Downflow hanging sponge (DHS) is one of the aerobic process that is being developed. Studies on the use of AnMBR-DHS for textile wastewater treatment are still limited. Therefore, the performance of AnMBR-DHS in certain variations of hydraulic retention time (HRT) and membrane flux for textile wastewater treatment, especially BOD, COD, and color removal is important to evaluate. In this study, a combination of AnMBR with a working volume of 5 L and DHS G3 with a working volume of 0.5 L is used for synthetic textile wastewater treatment with Remazol Black B azo dye. The membrane used is hollow fiber PVDF with pore size of 0.07 - 0.1 ?m. The experiments were carried out at room condition with variations of AnMBR HRT 12 and 24 hours, DHS HRT 1.4 and 2.8 hours, and membrane fluxes 2.65 and 5.21 liter/m2/h or LMH. Parameter which analyzed are BOD, COD, and color. The combination of AnMBR-DHS has been proven to be able to reduce BOD, COD, and color in synthetic textile wastewater significantly, namely around 95-98%, 93-96%, and 94-98%, respectively. Most COD, BOD, and colors in synthetic textile wastewater are reduced in the anaerobic AnMBR process. Variations in AnMBR HRT, DHS HRT, and variations in membrane flux did not result in a significant difference in the performance of BOD, COD, and color removal by AnMBR-DHS. However, the greater membrane flux and the smaller HRT cause a faster rate of formation of fouling on the membrane surface.